The administration of guidance programs in public secondary schools in Manila and Quezon City and its implications for education in Thailand - Shoowong, Wanida 1939- (s.n.], 1967)
This study presents an investigation of the administration of guidance programs in the public secondary schools of Manila and Quezon City in a view of relating the results to public general secondary schools in Thailand where the guidance programs are started a few years ago.